Analysis of Serum Vitamin D Level and Related Factors in Patients With Restless Legs Syndrome - Liu, Hui Miao; Chu, Miao; Liu, Chen Fei; Zhang, Ting; Gu, Ping (Frontiers in Neurology, 2021)
Objective To detect serum vitamin D (VitD) levels in patients with primary restless legs syndrome (RLS), and to analyze the relationship of VitD levels with the severity of RLS symptoms, sleep, anxiety and depression. Methods The serum 25-hydroxyvitamin D [25(OH)D] levels of 57 patients with primary RLS and the healthy physical examinees in our hospital during the same period were detected. The International Restless Legs Syndrome Study Group (IRLSSG) rating scale for measuring RLS severity and Pittsburgh Sleep Quality Index (PSQI) Scale, 24-item Hamilton Depression Rating Scale (HAMD24), and 14-item Hamilton Anxiety Scale (HAMA14) were used to assess the severity of symptoms, sleep, and emotional state of RLS patients. Based on VitD level and IRLSSG score, they were grouped for analysis. Results The serum 25 (OH) D level was significantly lower in RLS patients than in healthy controls, and the incidence of insufficient serum VitD levels was significantly higher in RLS patients than in healthy people (both P<0.05). The serum VitD level was significantly lower in (extremely) severe RLS patients than in mild to moderate RLS patients (P<0.05). The IRLSSG scale score and HAMD24 score were significantly higher in RLS patients with insufficient serum VitD levels than those with normal serum VitD levels (both P<0.05). Correlation analysis of IRLSSG scale score with serum VitD level and each scale score in RLS patients showed that IRLSSG scale score was negatively correlated with VitD level, but positively correlated with PSQI, HAMA14, and HAMD24 scores. The results of correlation analysis between serum VitD levels and each scale score in RLS patients indicated that serum VitD levels were negatively correlated with IRLSSG scale scores, PSQI scores, and HAMD24 scores. Conclusion The serum VitD level is generally lower in RLS patients than in healthy people, and lower serum VitD level is associated with more severe symptoms of RLS, worse quality of sleep, and worse depression.